2018
DOI: 10.1017/jfm.2018.490
|View full text |Cite
|
Sign up to set email alerts
|

Suspensions of finite-size neutrally buoyant spheres in turbulent duct flow

Abstract: We study the turbulent square duct flow of dense suspensions of neutrally-buoyant spherical particles. Direct numerical simulations (DNS) are performed in the range of volume fractions φ = 0−0.2, using the immersed boundary method (IBM) to account for the dispersed phase. Based on the hydraulic diameter a Reynolds number of 5600 is considered. We report flow features and particle statistics specific to this geometry, and compare the results to the case of two-dimensional channel flows. In particular, we observ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 70 publications
(103 reference statements)
3
17
0
Order By: Relevance
“…For φ = 5 and 10%, compared to the single phase NF case, the streamwise velocity fluctuations marginally increase above the wall-normal location y/H ≈ 0.2 while they decrease below y/H ≈ 0.2. Such a behaviour was also observed, albeit more pronounced, in [18] at φ = 5 and 10%. With further increase in φ, the streamwise velocity fluctuations reduce for all wall-normal locations in our study.…”
Section: Velocity Statisticssupporting
confidence: 58%
“…For φ = 5 and 10%, compared to the single phase NF case, the streamwise velocity fluctuations marginally increase above the wall-normal location y/H ≈ 0.2 while they decrease below y/H ≈ 0.2. Such a behaviour was also observed, albeit more pronounced, in [18] at φ = 5 and 10%. With further increase in φ, the streamwise velocity fluctuations reduce for all wall-normal locations in our study.…”
Section: Velocity Statisticssupporting
confidence: 58%
“…The simulations confirm the largest concentration at the core of the duct at φ = 20% and that the Reynolds stresses are typically lower than those of the single phase flow, as also generally found in this study. Fornari et al (2018a) suggest that turbulence is largely attenuated at this φ: turbulence production is reduced, but this is compensated by a large increase in energy injection due to particle-induce stresses.…”
Section: Discussionmentioning
confidence: 94%
“…To explain the cause for the non-monotonic pressure drop at the highest volume fraction φ = 20% and higher Re 2H (where the influence of gravity on pressure drop is negligible) we consider the variation of concentration and mean-streamwise velocity profile in the plane of the wall bisector, as sketched in figure 20. Velocity and concentration measurements have been performed for LP and MP only whereas a qualitative picture is proposed for SP based on the pressure drop measurements and the simulations in Fornari et al (2018a) for neutrally buoyant particles as their size in inner units (20δ ν ) is in range of our experiments for SP (15-37δ ν ). The simulations are, however, performed at a lower Re 2H = 5600 and the particle size in bulk units is 2H/d p = 18, similar to MP in experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, at constant Φ and pressure gradient, the flow rate reduced as the particle settling effect increased (lower Sh). It is also worth to note the recent simulations of [8] for neutrally buoyant particles in a square duct up to a volume fraction of 20%. These authors found that for Φ ≤ 10%, particles preferentially accumulate on the corner bisectors and turbulence production is enhanced, whereas at Φ = 20% particles migrate towards the core region and turbulence production decreases below the values for Φ = 5%.…”
Section: Introductionmentioning
confidence: 97%